The (big) Role of Family Constellations in Return Migration and Transnationalism - Bresena Kopliku Dema; Elvisa Drishti (Global Labor Organization (GLO), 2022)
Purpose: The Albanian migration has always reflected a family character, be that before 1945 when Albania was not yet completely isolated, as well as after 1990 when borders were reopened. This feature characterized all types of movement, internal or international, permanent or seasonal migration, return migration or transnational movements, and remigration. The role of the family has been very important in making decisions regarding migration and answering questions from why to how to migrate, from when to where, whom to ask for help or how to invest remittances. Design/methodology/approach: Based on the case study of a rural area in Northern Albania, The Administrative Unit of Dajç, this article explores in detail the roles of family and kinship on decisions regarding return migration, the re-adjustment process, remigration or transnational life. Findings: By exploring the role of the family context in remigration and vice-versa the article reflects that the family biography - including the lifestyle, plans for the future or expectations - has changed due to previous migration experiences or challenges and difficulties when returning to the home country. Originality/value: It demonstrates how individual decisions to migrate or to 'return home' are negotiated and supported within families making transnational life a family project. The article adopts a new approach in the Albanian Migration Studies which may be implied on broader areas for further research in the future.
Keywords: 330; Albania; family; migration; return; transnationalism